23rd International Conference on Offshore Mechanics and Arctic Engineering, Volume 2 2004
DOI: 10.1115/omae2004-51143
|View full text |Cite
|
Sign up to set email alerts
|

High Strength Linepipe With Excellent HAZ Toughness

Abstract: The API 5L-X65 steel plates for low temperature service were produced using the thermo-mechanical control process (TMCP) with the optimum micro-alloying addition. Featuring of the additions are as low amount of titanium, calcium, niobium, and vanadium as possible, for high heat affected zone (HAZ) toughness and strength. Controlling titanium and nitrogen and the Ti/N ratio, a large number of TiN dispersed finely are formed in steel and the austenite grain size near a weld fusion line is refined remarkably owin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…41 Jiao et al 42 stated that the best toughness achieved at Ti/N53 in high Nb pipeline steels and recommended the industry control of Ti/N in the range of 2-3. Hillenbrand et al 41 11 Effect of Ti/N ratio on grain size and toughness 40 Zhu et al further claimed that Ti content of the steel must be ,0?025% to avoid the detrimental effects on the HAZ toughness of the longitudinal weld seam. The above review advised that different Ti, N additions as well as Ti/N ratios were considered to be optimal for HAZ properties, especially toughness.…”
Section: Optimum Ti/n Ratio For Toughnessmentioning
confidence: 97%
See 1 more Smart Citation
“…41 Jiao et al 42 stated that the best toughness achieved at Ti/N53 in high Nb pipeline steels and recommended the industry control of Ti/N in the range of 2-3. Hillenbrand et al 41 11 Effect of Ti/N ratio on grain size and toughness 40 Zhu et al further claimed that Ti content of the steel must be ,0?025% to avoid the detrimental effects on the HAZ toughness of the longitudinal weld seam. The above review advised that different Ti, N additions as well as Ti/N ratios were considered to be optimal for HAZ properties, especially toughness.…”
Section: Optimum Ti/n Ratio For Toughnessmentioning
confidence: 97%
“…As shown in Fig. 11, recent work from Okastu et al 40 investigated X65 pipeline steels having Ti/N ratio in the range of 2–4. It appears that higher Ti/N ratio can lead to deteriorations in HAZ toughness and best CGHAZ toughness achieved at Ti/N = 2.…”
Section: Effects Of Ti N and Ti/n Ratio On Haz Toughnessmentioning
confidence: 99%
“…However, with an hypostoichiometric Ti addition (Ti/N=2), He and Baker 205 found that with a low finishing rolling temperature,800°C, excellent toughness and mechanical properties were obtained due to grain refinement and strain induced precipitation. Using the Ti/N ratio as a guide to avoiding poor toughness was also supported by the work of Okastu et al, 321…”
Section: Fig52 Near Herementioning
confidence: 88%
“…However, with an hypostoichiometric Ti addition (Ti/N = 2), He and Baker [205] found that with a low finishing rolling temperature, 800°C, excellent toughness and mechanical properties were obtained due to grain refinement and SIP. Using the Ti/N ratio as a guide to avoiding poor toughness was also supported by the work of Okastu et al [321] who investigated X65 steels with Ti/N ratios from 2 to 4. Although most investigations have considered the Ti/N ratio as a reasonable guide for obtaining MA steels with acceptable toughness levels, Shen and Hansen [322] concluded from their work, that any effects related to coarse TiN particles should be analysed using [Ti][N] product rather than Ti/N ratio.…”
Section: Welding Of Titanium Ma Steelsmentioning
confidence: 93%
“…[3] To enhance the toughness of HAZ, various techniques have been developed, relying on restricting austenite coarsening, stimulating intragranular nucleation, and reducing M/A constituent sizes. [4][5][6] Among them, developing an acicular ferrite (AF) dominant microstructure has been regarded as an effective measure, and frequently AF has been known as the optimal microstructure in steel HAZ and welds, because of its superior combination of strength and toughness. [7,8] AF was first found in steel welds as laths that nucleate heterogeneously on small nonmetallic inclusions and grow in many different directions from these point nucleation sites.…”
Section: Introductionmentioning
confidence: 99%